-4(u-4)=8u+40

Simple and best practice solution for -4(u-4)=8u+40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(u-4)=8u+40 equation:



-4(u-4)=8u+40
We move all terms to the left:
-4(u-4)-(8u+40)=0
We multiply parentheses
-4u-(8u+40)+16=0
We get rid of parentheses
-4u-8u-40+16=0
We add all the numbers together, and all the variables
-12u-24=0
We move all terms containing u to the left, all other terms to the right
-12u=24
u=24/-12
u=-2

See similar equations:

| 4+6x=21 | | |5x+3|=|x+11| | | (3/5)*e-6=(-2/5)e-3 | | p+17.12=2.33 | | 70=10(j+2) | | (3/5)*e-6=-2/5e-3 | | -4(s+19)=-12 | | 4d-12=28 | | (3/5)*e-6=-2/5(e-10)-7 | | 5-2+x=2x-3 | | |-w+6|=-7w | | 14u+-10u+-16u=-12 | | 7(x-4)+7=13x-6(x-3) | | 6x-17+48=90 | | p/3+-8=-6 | | 3x+31+2x-6=90 | | t/3-6=2 | | h/3-9=-7 | | (3/5)(e))-6=(-2/5)(e))-3 | | 18+h=36 | | -8=-8(c-90) | | -20+-9n=-92 | | (3/5)(e)-6=(-2/5)(e)-3 | | -j+4=-3 | | 4x+8x-42=105-9x | | f/7+56=47 | | 5.8=-4.5+x | | 3k-2=-2|k+2| | | 6-5s/3=s | | g/7-6=1 | | 5r-1=14 | | 4e+12=-e+7 |

Equations solver categories